2018
DOI: 10.4025/actascihealthsci.v40i1.34781
|View full text |Cite
|
Sign up to set email alerts
|

<b>Prevalence of self-reported <i>diabetes</i> and hypertension among users of primary health care services

Abstract: ABSTRACT. The objective of this cross-sectional study was to estimate the prevalence of self-reported hypertension and diabetes among the users of primary health care services of Southeast Ribeirão Preto, State of São Paulo, Brazil, and to identify variables which may be associated with these chronic conditions. A stratified sample of 1,055 adult individuals was surveyed, with the resulting associations being examined by using log-binomial regression models and then expressed as prevalence ratios (PRs). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…In the present study, self-reported DM prevalence among females was 24.6% and among males was 28.6%. These values are very close to that obtained in a previous study 22 among users of primary health care facilities of Ribeirão Preto (24.3% for the overall population of individuals aged 60 years or older). A former study based on home interviews conducted in 1996 in Ribeirão Preto, showed a self-reported DM prevalence among women of 23.1% among females and 19.2% among males aged 60 years or older 23 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, self-reported DM prevalence among females was 24.6% and among males was 28.6%. These values are very close to that obtained in a previous study 22 among users of primary health care facilities of Ribeirão Preto (24.3% for the overall population of individuals aged 60 years or older). A former study based on home interviews conducted in 1996 in Ribeirão Preto, showed a self-reported DM prevalence among women of 23.1% among females and 19.2% among males aged 60 years or older 23 .…”
Section: Discussionsupporting
confidence: 89%